The Effect of Azolla microphylla Liquid Fertilizer on the Growth of Nannochloropsis oculata Populations on a Laboratory Scale - Padli, Fery; Tanjung, Afrizal; Nasution, Syafruddin (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Nannochloropsis oculata is a microalgae often used as natural food for fish larvae. In general, microalgae cultivation uses standardized Walne fertilizer. This research uses an experimental method to determine the effect of administering Azolla microphylla liquid fertilizer at different doses on the growth of the N. oculata population on a laboratory scale. This experiment was conducted from September to October 2022 at the Experimental Pond Laboratory, Biotechnology Laboratory, Marine Biology Laboratory, Department of Marine Science, Faculty of Fisheries and Marine, Universitas Riau. This research used a Simple, Completely Randomized Design (CRD) with four treatment levels and three replications. The treatment used A. microphylla liquid fertilizer with doses A (2 mL), B (3 mL), C (4 mL), and D (Walne fertilizer control). The results showed that the highest population density was in treatment D (control) on day 6 with a value of 483.5 x 105 (cells/mL) and treatment C (4 mL A.microphylla fertilizer) on day 5 with a value of 437.3 x 105 (cells/mL). The results of the ANOVA test showed a significance value of 0.007 < 0.05, which indicated a significant difference between the treatment of A. microphylla liquid organic fertilizer at different doses on the density of N.oculata. Relatively, the growth rate of N. oculata in treatment D (Walne fertilizer) was still the highest, with a value of 170.868%, and treatment C, with a percentage of 145.005%. Furthermore, the specific growth rate in treatment B was the highest, with a value of 1.730% on day 4. The Walne liquid fertilizer treatment, which was the control, was still higher and dominated the population and growth rate of N. oculata and could not be replaced with A. microphylla liquid fertilizer